Identifikasi Pemanfaatan Lahan di Kawasan Pesisir Kecamatan Tamalate, Kota Makassar - Adnan Anwar; Baharuddin Koddeng; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
Indonesia is one of the largest archipelago countries in the world which has approximately 17,508 islands with a coastline of 81,000 km. Indonesia's coastal and marine resources are one of the basic capital development potentials of Indonesia in addition to terrestrial natural resources. This study aims to identify morphological developments and land demand for the next 10 years in the coastal area of ​​Tamalate District. The analytical method used in this research is descriptive, qualitative, spatial, and regional carrying capacity analysis. The results showed that the coastline on the edge of Tamalate District had experienced changes caused by anthropogenic factors which were geomorphological processes caused by human activities. Changes in the use of land functions are shown in the change of agriculture into housing in the years 1999-2012. Furthermore, the projection of the population in the next 10 years is 13.1%. This amount is still very possible for areas with carrying capacity of residential land where the land demand is around 0.086 ha / person.